Data analytics and efficiency of value-added tax revenue generation in Nigeria - Obasi, Mba Okoko; Olajide, Dada, Samuel; Anaekenwa, Aguguom Theophilus; Ifayemi, Olayinka Moses (Asian Journal of Economic Modelling, 2025)
The efficiency of Value-Added Tax (VAT) revenue generation serves as a vital and stable source of income for the Nigerian government, particularly in addressing the fiscal gap created by fluctuating oil revenues. Despite this, the government has not fully harnessed the potential of VAT to deepen revenue generation. Existing studies highlight that the application of data analytics tools presents opportunities to enhance VAT efficiency in the country. This study investigated the impact of data analytics on the efficiency of VAT revenue generation in Nigeria using a survey research design. The target population, estimated at 2,000,000, comprised staff of the Federal Inland Revenue Service, professional accountants, tax consultants, and individuals knowledgeable in data analytics and tax matters. A sample of 400 respondents was determined using Taro Yamane’s formula, with purposive sampling applied for participant selection. Data were collected using a structured questionnaire, and the instrument’s validity and reliability were established through KMO and Bartlett’s tests, with Cronbach’s alpha values between 0.798 and 0.880. A 96% response rate was recorded. Descriptive statistics showed strong agreement on the positive effect of data analytics, while regression results confirmed a significant impact on VAT efficiency. The study recommended prioritizing VAT efficiency enhancement to boost government income.